The Use of Spinning Letter Learning Media to Increase Students' Interest in Learning to Read in Indonesian Language Learning in Elementary Schools - Hardiansyah, Framz; Qinayah, Lini; Nafiah, Sholihatun; Ilyana, Zaina; Ahmad, Alfarisi (Global Action and Education for Society, 2026)
The use of letter rotating wheel learning media is a strategy to increase the interest in learning to read of grade 2 students at SDN Pabian IV. This study aims to explore the effectiveness of the media in helping students recognize letters and words, as well as increasing their engagement in the learning process. The method used in this research is qualitative, with data collection techniques through observation, documentation and interviews. The results showed that 91% of students actively participated in activities using the letter rotating wheel media, indicating an increase in students' interest and engagement in learning to read. This media not only makes learning more interesting and interactive, but also supports multisensory learning that strengthens students' memory of the material. Despite challenges in preparation and time management, the use of the letter rotating wheel media proved effective in improving students' reading skills. Therefore, it is recommended that teachers integrate this media in Indonesian language learning to achieve better results.